Capturing the value of forest carbon for local livelihoods - Smith, J.; Scherr, Sara J. (2003)
This article contributes to the debate on the social implications of carbon forestry projects by showing that tradeoffs exist between social benefits of projects and their cost-effectiveness. Large scale industrial plantations and strict forest protection are economically viable, but pose the highest social risks. Socially beneficial projects are less cost-effective because of their higher transaction costs. Enabling policies are also required for their success. Regulation of carbon markets will therefore be required to reduce social risks and enhance benefits. The authors propose a number of regulatory and proactive measures and justify them on the basis of market imperfections and concepts of sustainable development.